Analysis of Clean Water Quality and Quantity for Domestic Needs in Rutong - Kaihena, Frida; Tetelepta, Edward Gland; Manakane, Susan Evelin (Jurnal Pendidikan Geografi Unpatti, 2024)
This study evaluates the quality and quantity of clean water available for domestic needs in Rutong Village, South Leitimur District, Ambon City. This study uses a quantitative descriptive research approach to provide a comprehensive overview of the clean water situation in the area. The population of this study comprises the residents of Rutong Village, with samples randomly selected from 10 households using Water Waihula and Water Cabang Dua or Saplaring. Data collection techniques include observation, documentation, and interviews. Quality analysis of clean water involves laboratory tests covering physical, biological, and chemical measurements. Quantity analysis is conducted through water flow rate calculations while predicting water demand utilizing equations based on population and standard water requirements per individual. Test results indicate that the quality of clean water in Rutong Village meets the standards set by Permenkes No. 32 of 2017. All physical, chemical, and biological parameters comply with permissible maximum standards, including odour, taste, TDS, turbidity, temperature, colour, iron, hardness, chloride, zinc, and coliform bacteria. However, despite meeting quality standards, it was found that the quantity of clean water available still needs to meet the community's needs sufficiently. On average, residents can only use 120 litres of water per day, indicating a need for improvement in the clean water supply to adequately meet the community's needs.